Synthesis of some new spirocyclic β-lactam and spirocyclic thiazolidin-4-one derivatives - Elkanzi, Nadia Ali Ahmed; Yosef, Hisham Abdallah Abd El-Monem; Mohamed, Nesrin Mahmoud Morsy (European Journal of Chemistry, 2013)
Selective oxidation of 4-amino-2-methyl-5,10-dioxo-1,5,10,10a-tetrahydrobenzo[g]-quinoline-3-carbonitrile (1) with selenium dioxide provided, 4-amino-2-formyl-5,10-dioxo-1,5,10,10a-tetrahydrobenzo[g]quinoline-3-carbonitrile (2). The one-pot reaction of compound 2 with ethyl cyanoacetate and thiourea in ethanol yielded 4-amino-2-(5-cyano-6-oxo-2-thioxo-1,2,3,6-tetrahydropyrimidin-4-yl)-5,10-dioxo-1,5,10,10a-tetrahydrobenzo[g]-quinoline-3-carbonitrile (3). The cycloaddition reaction of chloroacetic acid with compound 3 yielded 7-(4-amino-3-cyano-5,10-dioxo-1,5,10,10a-tetrahydrobenzo-[g]quinolin-2-yl)-3,5-dioxo-3,5-dihydro-2H-thiazolo[3,2-a]pyrimidine-6-carbonitrile (4). Moreover, Ehrlich-Sachs condensation reaction of compound 4 with the aromatic nitroso compounds 5a-c gave the corresponding new Schiff bases 6a-c. Staudinger’s ketene-imine cycloaddition reaction of compounds 6a-c with chloroacetyl chloride afforded the corresponding spiro[chloroazetidinethiazolopyrimidine] derivatives, 7a-c. On the otherhand, cycoladdition reaction of thioglycolic acid with Schiff bases 6a-c yielded the corresponding spiro[thiazolidinethiazolopyrimidine] derivatives, 8a-c. Structures of the new compounds were elucidated by compatible analytical and spectroscopic (IR, 1H NMR and MS) measurements. Moreover, the reaction mechanisms that account for formation of the synthesized compounds have been discussed.